1997
DOI: 10.1046/j.1365-2362.1997.1380688.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of insulin on transport and metabolism of glucose in skeletal muscle from hyperthyroid and hypothyroid rats

Abstract: The effects of insulin on the rates of glucose disposal were studied in soleus muscles isolated from hyper- or hypothyroid rats. Treatment with triiodothyronine for 5 or 10 days decreased the sensitivity of glycogen synthesis but increased the sensitivity of lactate formation to insulin. The sensitivity of 3-O methylglucose to insulin was increased only after 10 days of treatment and was accompanied by an increase in the sensitivity of 2-deoxyglucose phosphorylation; however, 2-deoxyglucose and glucose 6-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
7

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 35 publications
7
64
0
7
Order By: Relevance
“…In agreement with previous results, glucose tolerance was impaired in the hyperthyroid subjects (2, 16); this is due to the insulin resistance primarily at the liver since glucose uptake in peripheral tissues is generally found to be either normal or increased (2,16,17).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous results, glucose tolerance was impaired in the hyperthyroid subjects (2, 16); this is due to the insulin resistance primarily at the liver since glucose uptake in peripheral tissues is generally found to be either normal or increased (2,16,17).…”
Section: Discussionsupporting
confidence: 92%
“…In hyperthyroidism, absolute rates of glucose transport in peripheral tissues (such as muscle or adipose tissue) are found to be increased, in order to adapt to high energy demand (2,16,17). Our results suggest that hyperthyroidism increases the sensitivity of the recruitment of GLUT3 and GLUT4 transporters to the cell surface in response to IGF-I, thus contributing to increased glucose transport rates.…”
Section: Discussionmentioning
confidence: 65%
“…In HR, the absolute rates of insulin-stimulated glucose transport in peripheral tissues (such as muscle or adipose tissue) have generally been found to be normal or increased, in order to adapt to high energy demand (3,25). However, we have recently shown that glucose uptake in muscle in HR is indeed resistant to insulin, but this defect is masked by a marked increase in blood flow (4); this could be attributed to the dramatic decrease in intracellular pathways of insulin-stimulated glucose metabolism (such as glycogen synthesis) (25,26). In addition, tumor necrosis factor a and interleukin 6 may contribute to insulin resistance in the metabolism of both lipids and glucose in HR (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several investigations have demonstrated a stimulatory effect of T3 on insulin-stimulated glucose transport and/or phosphorylation in muscle [4,5], on the insulin-sensitive muscle/fat glucose transporter, GLUT4 [4,6], and on glycolysis in isolated muscle [5]. Other data showed decreased insulinstimulated glucose transport and/or phosphorylation, as well as a lower rate of glycolysis in isolated muscles from hypothyroid animals, as induced by propylthiouracil (PTU) administration [5,7]. Similar findings were obtained when studying isolated adipocytes from hypothyroid patients, as these cells exhibited decreased insulin responsiveness with regard to glucose utilisation.…”
Section: Introductionmentioning
confidence: 99%